SPATIAL ANALYSIS OF REGIONAL DEVELOPMENT OF NGEMPLAK DISTRICT 2013-2023 - Iemaaniah, Zuhdiyah Matienatul; Selvia, Siska Ita (JURNAL AGRIMANSION, 2024)
Development policies influence the rate of regional development. Population growth and the affordability of areas to urban centers determine development policies. Urban areas that have experienced rapid development will gradually influence the surrounding peri-urban areas. The expansion of urban areas leads to suburban areas, starting from the expansion of residential areas. This research aims to determine regional development and regional development priorities in Ngemplak District. This research is qualitative research with comparative and spatial analysis. The results of this research are 1) the level of regional development in Ngemplak District is categorized into 3, namely developed, medium and underdeveloped areas. Villages in the advanced category include Sawahan Village, Ngesrep Village, Pandeyan Village, Kismoyoso Village, Donohudan Village and Gagaksipat Village. Those included in the medium category are Dibal Village, Manggung Village and Sobokerto Village, and those included in the underdeveloped villages are Sindon Village, Ngargorejo Village and Giriroto Village. 2) There are 3 development priorities, namely priority 1 for underdeveloped villages, priority II for medium level villages and priority III for advanced villages.